Novel polymorphic microsatellite markers in section Caulorrhizae (Arachis, Fabaceae) - Palmieri, D. A. [UNESP] (2005)
This work reports the characterization of 11 polymorphic microsatellite loci in section Caulorrhizae. The primer pairs were designed from Arachis pintoi and showed full transferability to Arachis repens species. These new markers were used to evaluate the genetic diversity in germplasm (accessions and cultivars) of section Caulorrhizae. This new set of markers detected greater gene diversity than morphological and molecular markers such as AFLP (amplified fragment length polymorphism) and RAPD (rapid analysis of polymorphic DNA) previously used in this germplasm. © 2005 Blackwell Publishing Ltd.